Asas Tunggal Pancasila dan Upaya Memaknai Kembali “Stabilisasi” Politik Indonesia - Amsar A. Dulmanan (Budapest International Research and Critics University, 2015)
This paper deals with the single principle of Pancasila and efforts to redefine the